Comparative Genome and Evolution Analyses of an Endangered Stony Coral Species Dendrophyllia cribrosa Near Dokdo Islands in the East Sea. (26th August 2022) - Kim, Jungeun; Choi, Jae Pil; Kim, Min Sun; Jo, Yejin; Min, Won Gi; Woo, Seonock; Yum, Seungshic; Bhak, Jong
Abstract: Stony corals often harbor intracellular photosynthetic dinoflagellate algae that receive dissolved inorganic nutrients. However, Dendrophyllia cribrosa is a nonsymbiotic stony coral distributed in the western Pacific. We assembled a chromosome-level D. cribrosa genome using PacBio and Hi-C technologies. The final assembly was 625 Mb, distributed on 14 chromosomes, and contained 30, 493 protein-coding genes. The Benchmarking Universal Single-Copy Orthologs analysis revealed a percentage of 96.8 of the metazoan genome. A comparative phylogenetic analysis revealed that D. cribrosa, which lacks symbionts, evolved to acquire cellular energy by expanding genes related to acyl-CoA metabolism and carbohydrate transporters. This species also has expanded immune-related genes involved in the receptor protein tyrosine kinase signaling pathway. In addition, we observed a specific expansion of calcification genes, such as coral acid-rich proteins and carbonic anhydrase, in D. cribrosa . This high-quality reference genome and comparative analysis provides insights into the ecology and evolution of nonsymbiotic stony corals.